Previous Preeclamptic Pregnancy and Chronic Hypertension Affects Current Preeclampsia at a Public Health Center in Bojonegoro, Indonesia - Indrayanti Indrayanti; Abdul Latip; Masfuah Ernawati; Mariya Ulfah (Health Dynamics, 2026)
Background: Preeclampsia is one of the leading causes of maternal mortality and occurs frequently in Indonesia. The high maternal mortality rate (MMR) reflects the low quality of health services during pregnancy, childbirth, and the postpartum period. This study aimed to analyze the risk factors associated with the incidence of preeclampsia among pregnant women at the Public Health Center in Sukosewu, Bojonegoro, Indonesia. Methods: This study used a cross-sectional design. The samples consisted of 120 pregnant women at the Public Health Center in Sukosewu, Bojonegoro District, Indonesia. Odds ratio and logistic regression tests were applied in this study. Results: Gravida (p = 0.046) and a history of chronic hypertension (p = 0.015) had a significant positive effect (p < 0.05) on the incidence of preeclampsia. Meanwhile, family history (p = 0.079), twin pregnancy (p = 0.999), gestational interval (p = 0.261), age (p = 0.132), BMI (p = 0.336), MAP (p = 0.997), history of hypertension during pregnancy (p = 0.260), and history of DM (p = 1.000) showed no significant effect on the incidence of preeclampsia. Conclusion: The incidence of preeclampsia among pregnant women at the Public Health Center in Sukosewu, Bojonegoro, Indonesia, was associated with the risk factors of previous preeclampsia and a history of chronic hypertension during pregnancy.